Comparative molecular cytogenetics in Cetartiodactyla - Rubes, J; Musilova, P; Kopecna, O; Kubickova, S; Cernohorska, H; Kulemsina, A I (Cytogenetic and genome research, 2012)
Cetartiodactyla comprises Artiodactyla (even-toed ungulates) and Cetacea (whales, dolphins and porpoises). Artiodactyla is a large taxon represented by about 200 living species ranked in 10 families. Cetacea are classified into 13 families with almost 80 species. Many publications concerning karyotypic relationships in Cetartiodactyla have been published in previous decades. Formerly, the karyotypes of closely related species were compared by chromosome banding. Introduction of molecular cytogenetic methods facilitated comparative mapping between species with highly rearranged karyotypes and distantly related species. Such information is a prerequisite for the understanding of karyotypic phylogeny and the reconstruction of the karyotypes of common ancestors. This study summarizes the data on chromosome evolution in Cetartiodactyla, mainly derived from molecular cytogenetic studies. Traditionally, phylogenetic relationships of most groups have been estimated using morphological data. However, the results of some molecular studies of mammalian phylogeny are discordant with traditional conceptions of phylogeny. Cetartiodactyls provide several examples of incongruence between traditional morphological and molecular data. Such cases of conflict include the relationships of the major clades of artiodactyls, the relationships among the extant families of the suborder Ruminantia or the phylogeny of the family Bovidae. The most unexpected aspect of the molecular phylogeny was the recognition that Cetacea is a deeply nested member of Artiodactyla. The largest living order of terrestrial hoofed mammals is the even-toed hoofed mammals, or Artiodactyla. The artiodactyls are composed of over 190 living species including pigs, peccaries, hippos, camels, llamas, deer, pronghorns, giraffes, sheep, goats, cattle and antelopes. Cetacea is an order of wholly aquatic mammals, which include whales, dolphins and porpoises. Cetartiodactyla has become the generally accepted name for the clade containing both of these orders.
Keywords: Ruminants; Chromosome Painting; karyotyp; Chromosomes, Mammalian; přežvýkavci; Karyotype; skot; cytogenetické vyšetření; Swine; Cetacea; zvířata; malování chromozomů; fylogeneze; Cattle; Species Specificity; prasata; Artiodactyla; druhová specificita; savčí chromozomy; Phylogeny; Cytogenetic Analysis; Animals